Anticoagulant therapy for recurrent in-stent thrombosis following carotid artery stenting: A case report. Issue 5 (October 2017) - Miyakoshi, Akinori; Toda, Hiroki; Hayase, Makoto; Kawauchi, Takeshi; Oichi, Yuki; Hattori, Etsuko
We report a case in which strict anticoagulant therapy management was useful for a recurrent in-stent thrombosis after carotid artery stenting (CAS). An 84-year-old man presented with cognitive decline that progressed rapidly over two months. Head magnetic resonance imaging showed an acute-stage infarct occurring frequently in the right cerebral hemisphere, and he underwent hospitalization and treatment. On neck magnetic resonance angiography (MRA), severe stenosis was found at the origin of the right internal carotid artery. Since he took aspirin, clopidogrel, and a statin after placement of an indwelling coronary stent, we treated him by adding argatroban and edaravone drip therapy to his existing medication. CAS was performed on day 15 of the hospitalization. A small in-stent thrombosis with plaque protrusion was observed on a carotid sonogram performed at the second day after CAS, and re-examination at the seventh day confirmed enlargement of the lesion and an increase in peak systolic velocity; thus, a second CAS procedure was performed on the same day. After the second CAS, oral cilostazol was added for triple antiplatelet therapy (TAPT), but as the in-stent thrombosis increased further, we started a continuous infusion of heparin with the goal of an activated partial thromboplastin time (APTT) of 50 to 65 seconds. After starting heparin, the lesion did not progress; after 14 days of continuous heparin infusion, the patient was switched to TAPT, and regression of the plaque was confirmed. This case demonstrated to us that controlled anticoagulation therapy can be an effective treatment for cases in which a thrombus recurs within a stent after CAS.